1993
DOI: 10.1093/clinids/17.supplement_1.s163
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation In Vivo by the Mycoplasma arthritidis Superantigen, MAM

Abstract: Mycoplasma arthritidis produces a potent superantigen (MAM) that activates specific murine and human T lymphocytes to proliferate and secrete lymphokines. We show here that MAM also influences both T- and B-cell functions in vivo. Lymphocytes from mice injected with MAM exhibit a suppression of proliferative responses to MAM in vitro but only a partial suppression of responses to other mitogens. This T-cell anergy not only decreased contact sensitivity to dinitrofluorobenzene but also prolonged survival of ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
4
15
1
Order By: Relevance
“…A similar in vitro anergy in peripheral T lymphocytes has been described in the mouse model for SEB [29]. Furthermore, MAS not only influences T-cell functions, but also increases monocyte activity by enhancing the production of IL-6 and IL-1/3 [11,12,30].…”
Section: Discussionsupporting
confidence: 65%
“…A similar in vitro anergy in peripheral T lymphocytes has been described in the mouse model for SEB [29]. Furthermore, MAS not only influences T-cell functions, but also increases monocyte activity by enhancing the production of IL-6 and IL-1/3 [11,12,30].…”
Section: Discussionsupporting
confidence: 65%
“…They have been implicated in immunomodulatory actions such as immunosuppression and induction of autoimmune diseases 6,26,27) . The present study showed that mycoplasma species isolated from saliva samples obtained from HIV(‫)ם‬ and HIV(‫)מ‬ subjects produced HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…Production of superantigens and of heat shock proteins (HSPs) is closely associated with changing host responses [1][2][3][6][7][8]21,22,26,27) . This study was designed to evaluate the significance of infections by M. salivarium and M. orale in HIV(‫)ם‬ patients.…”
Section: Mycoplasma Salivarium and Mycoplasma Oralementioning
confidence: 99%
“…MAM has been found to enhance the responses of human and mouse B cells (85,97,461). Although MAM by itself did not trigger significant stimulation of isolated B lymphocytes, CD4…”
Section: Activation Of Immune Cells By Mitogenic Mycoplasmasmentioning
confidence: 99%
“…The potential of M. arthritidis to cause acute and chronic inflammatory arthritis in rodents, together with the discovery that this mycoplasma produces the potent superantigen MAM (83), prompted Cole and associates to investigate the effects of MAM in vivo. Although MAM by itself failed to induce chronic arthritis in mice (85), the investigators found that intra-articular administration of MAM to DA rats produced local joint inflammation and swelling that resolved a week later (67). Systemic injection of MAM into mice caused a temporary anergy of cell-mediated immune responses with a simultaneous enhancement of B-cell activation and differentiation (85).…”
Section: Autoimmune Manifestationsmentioning
confidence: 99%